Hubungan Kualitas Tidur Dengan Postpartum Blues Pada Ibu Postpartum Di Puskesmas Jagir Surabaya - Septianingrum, Yurike; Damawiyah, Siti (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2019)
Introduction: Postpartum blues have been considered as a normal response to hormonal changes in the mother, but if left untreated can immediately lead to postpartum depression. One of the factors that caused postpartum blues is poor sleep quality. The purpose of this study was to analyze the correlation between sleep quality and postpartum blues among postpartum mothers in Puskesmas Jagir Surabaya. Method: This research is an analytic observational with cross sectional approach. The subjects of this study were all postpartum mothers who visited at Puskesmas Jagir in July 2019 and were selected through purposive sampling according to inclusion and exclusion criteria. The instruments used were PSQI (Pittsburgh Sleep Quality Index) and EPDS (Edinburgh Postnatal Depression Scale). Data were analyzed using the Wilcoxon test and Mann-Whitney U test. Result and Analysis: The results showed that: 1) Almost all postpartum mothers had poor sleep quality 2) There was no correlation between sleep quality and postpartum blues (p = 1). Conclusion: There was no relationship between sleep quality and postpartum blues among postpartum mothers at Puskesmas Jagir Surabaya. Future studies are expected to look for the factors that most influence postpartum blues and it is hoped that Puskesmas routinely conduct postpartum blues screening to prevent postpartum depression. Keywords: endorphin massage, menstrual pain, primary dysmenorrhea